Determinants of Motivation for Field Placement among Vietnamese Social Work Students: A Risk and Protective Factors Analysis - Ngoc Nguyen (Indonesian Social Work Consortium (ISWC), 2026)
Social work education in Vietnam is still developing, with field education emerging as a key area needing attention. Despite the central role of field placement in professional training, limited research has examined factors influencing students’ motivation to engage in field education. This study investigates the risk and protective factors associated with social work students’ motivation for field placement in Vietnam. A binary logistic regression analysis was conducted with 541 undergraduate social work students aged 18–28 from eleven universities nationwide. Guided by an ecological perspective, the study examined whether stress, assignment of unprofessional tasks, supervisor availability, and opportunities to apply classroom knowledge and skills were associated with students’ motivation for field placement. The findings indicate that stress and the assignment of unprofessional tasks significantly reduced students’ motivation, whereas opportunities to apply classroom learning in practice and supervisor availability significantly enhanced motivation. Supervisor availability emerged as the strongest positive predictor of motivation. These results suggest that students’ motivation is shaped not only by individual experiences but also by the quality of their learning environment and supervisory support. The findings highlight the need to strengthen field education by improving supervision, reducing placement-related stressors, providing meaningful learning opportunities, and integrating theory and practice more effectively. Such efforts may enhance student engagement and contribute to the development of a competent social work workforce in Vietnam and similar emerging professional contexts.